Recommendations for Developing Ecotourism in Can Gio Mangrove Biosphere Reserve of Ho Chi Minh city - Huynh Tan Hoi (International Journal of Modern Agriculture, 2021)
Can Gio Biosphere Reserve-a suburban district of Ho Chi Minh City, Vietnam, has been recognized as a world biosphere reserve by UNESCO since 2000. Can Gio has been built into an ecotourism place with a rich flora and fauna, rich historical culture while ensuring ecological balance, attracting tourists and greatly contributing to the development of the city’s tourism industry. In terms of conditions for designing and organizing attractive tours with rich products and services, Can Gio has not been exploited effectively. The number of visitors to Can Gio is still modest, this place is only exploiting ecotourism, there is almost no excellent entertainment, shopping and resort. Although there are so many advantages, the exploitation and investment are not in the right range, therefore the potential here has been wasted over the years. We should have many more tourist products and services in order to attract tourists to this destination. The article is completed based on data from studies and actual survey process. The results show that the potential for tourism development here is huge and requires further breakthroughs in thinking and action.